2011
DOI: 10.1038/onc.2011.551
|View full text |Cite
|
Sign up to set email alerts
|

MiR-135a functions as a selective killer of malignant glioma

Abstract: Glioma is the most common and fatal primary brain tumor. Thus far, therapeutic strategies to efficiently and specifically antagonize glioma are limited and poorly developed. Here we report that glia-enriched miR-135a, a microRNA that is dramatically downregulated in malignant glioma and correlated with the pathological grading, is capable of inducing mitochondria-dependent apoptosis of malignant glioma by regulating various genes including STAT6, SMAD5 and BMPR2, as well as affecting the signaling pathway down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
62
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 39 publications
3
62
0
Order By: Relevance
“…MiR135a is downregulated in androgene-dependent versus androgene-independent prostate cancer cells [18]. Though miR-135a functions in a tumor suppressor in several cancer cells such as renal cell carcinoma [19] or glioma cell [20], it has not fully investigated in prostate cancer cells. Thus, in the present study, the underlying apoptotic mechanism by combination of Tanshinone I and TRAIL was studied mainly in highly aggressive DU145 and PC-3 prostate cancer cells in association with upregulation of death receptors and microRNA 135a-3p.…”
Section: Introductionmentioning
confidence: 99%
“…MiR135a is downregulated in androgene-dependent versus androgene-independent prostate cancer cells [18]. Though miR-135a functions in a tumor suppressor in several cancer cells such as renal cell carcinoma [19] or glioma cell [20], it has not fully investigated in prostate cancer cells. Thus, in the present study, the underlying apoptotic mechanism by combination of Tanshinone I and TRAIL was studied mainly in highly aggressive DU145 and PC-3 prostate cancer cells in association with upregulation of death receptors and microRNA 135a-3p.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, to increase the efficiency of this kind of treatment, nucleic acid drugs can be modified to be more lipophilic that improves their intracellular penetration. Although modest compared with pretreatment model, the intratumoral injection of cholesterylated tumor suppressor miRNA mimics has been successful in regression of tumors in the post treatment xenograft model (18). Nonetheless, combined with the ease and simplicity of the drug delivery to a given tumor site in oral cavity, the use of antagomir-155 could have enormous potential to evolve for further drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Being a multigenic disease, the single gene-based therapy of OSCC may fall short in therapy (18). Recent studies have shown that a growing class of noncoding RNAs called microRNAs (miRNAs) are involved in posttranscriptional regulation of genes (19).…”
mentioning
confidence: 99%
“…(33) According to this report, miR-135a is frequently downregulated in malignant glioma, with its expression negatively correlated to pathological grading, and can induce mitochondria-dependent apoptosis targeting STAT6, SMAD5, and BMPR2. These results are consistent with our current data.…”
Section: Discussionmentioning
confidence: 99%